Estimating the real world daily usage and cost for exenatide twice daily and liraglutide in Germany, the Netherlands, and the UK based on volumes dispensed by pharmacies - McDonell AL; Kiiskinen U; Zammit DC; Kotchie RW; Thuresson PO; Nicolay C; Haslam T; Bruinsma M; Janszen-Van Oosterhout AJ; Otto T (Dove Medical Press, 2015)
Amanda L McDonell,1 Urpo Kiiskinen,2 Danielle C Zammit,3 Robert W Kotchie,1 Per-Olof Thuresson,3 Claudia Nicolay,4 Thomas Haslam,1 Michiel Bruinsma,5 Anne-Jeanine Janszen-Van Oosterhout,6 Thorsten Otto41IMS Health, London, UK; 2Eli Lilly and Company, Helsinki, Finland; 3IMS Health, Basel, Switzerland; 4Eli Lilly and Company, Bad Homburg, Germany; 5IMS Health, Rotterdam, the Netherlands; 6Eli Lilly Nederland, Houten, the NetherlandsBackground: Glucagon-like peptide-1 (GLP-1) receptor agonists are indicated for improvement of glycemic control in adults with type 2 diabetes. Cost is one aspect of treatment to be considered, in addition to clinical benefits, when selecting optimal therapy for a patient. The objective of this study was to estimate the average dose usage and real world daily cost of the GLP-1 receptor agonists, exenatide twice daily and liraglutide once daily, in Germany, the Netherlands, and the UK.Methods: Administrative databases were used to source the data from longitudinal records of dispensed prescriptions. Data were extracted from the IMS Longitudinal Prescription database which captures details of prescriptions dispensed in pharmacies. Information on the dispensed quantity of each product was used to estimate average daily usage per patient. Daily dose usage was multiplied by the public price per unit to estimate daily cost.Results: The dispensed volume in Germany corresponded to a mean dispensed daily dose of 16.81 µg for exenatide twice daily and 1.37 mg for liraglutide (mean daily cost €4.02 and €4.54, respectively). In the Netherlands, average dispensed daily doses of 17.07 µg and 1.49 mg were observed for exenatide twice daily and liraglutide (mean daily cost €3.05 and €3.97, respectively). In the UK, the mean dispensed volume corresponded to a daily usage of 20.49 µg for exenatide twice daily and 1.50 mg for liraglutide (mean daily cost £2.53 and £3.28, respectively).Conclusion: Estimates of average daily dispensed doses of GLP-1 receptor agonists derived from pharmacy data in real world settings corresponded to the dosing recommendation of the summaries of product characteristics. Nevertheless, the mean daily cost of exenatide twice daily was lower than that of liraglutide in Germany, the Netherlands, and the UK. Such estimates can be used to inform health care decision-makers on the real world usage and cost of medications effective in achieving glycemic control in patients with type 2 diabetes.Keywords: type 2 diabetes, exenatide twice daily, liraglutide, dosage, cost, real world